From stimulation to attenuation: exposure mode-dependent conjugative transfer of antibiotic resistance gene under tetrabromobisphenol A-induced stress - Mengmeng Wang; Jie Yang; Shaoping Kuang; Chujin Ruan; Xiaoying Hu; Bo Zhang; Jingqiu Liao; Jianhua Guo; Pedro J.J. Alvarez; Pingfeng Yu (Water Research, 2026)

Preparation of N-doped activated carbon from enzymatic hydrolysis lignin using Mannich reaction and H3PO4 activation - Asim Waseem; Yang Li; Shaoping Xu; Kechao Wang; Haoquan Hu (Biomass and Bioenergy, 2026)

Comprehensive prevention and control technologies for karst tunnel construction safety: integration of advanced forecasting, monitoring, and emergency response - Yaodong Luo; Bing Luo; MingJun Li; Tiansi Zhang; Shaoping Yang; Luyao Ma; Bihe Zhang; Haoyan Zhang; Saeed Rehman (Carbonates and Evaporites, 2026)

Oral administration of dopamine boosts anti-Vibrio immunity in shrimp through Dorsal pathway activation - Zi-ang Wang; Shun Liu; Zexu Zhao; Xiaojia Liao; Linwei Yang; Hongliang Zuo; Shaoping Weng; Jianguo He; Xiaopeng Xu (Fish & Shellfish Immunology, 2026)

Enhanced Monosaccharide Profile and Anti-Alcoholic Liver Injury Activity in the Liquid Fermentation of Ecklonia kurome by Inonotus hispidus - Baohong Wei; Xue Yang; Jia Liu; Wanghua Bi; Shaoping Wang; Shuman Hu; Xiaoqing Ma; Wenzhe Yang; Changyun Wang; Lin Ju; Huashi Guan (Journal of Ocean University of China, 2026)

Flavor formation and microbial community dynamics in Dong ethnic fermented Anyu - Fenghong Li; Kelang Kang; Qun Huang; Xin li; Shaoping Deng; Yingjuan Wei; Hui Yang; Meijuan Yu (Food Research International, 2025)

Modulation of the gut-skin axis by polysaccharides: Mechanisms and therapeutic potential in immune-related skin diseases - Chen Haiming; Liao Yijing; Tang Bin; Ma Xiaoyu; Li Hailun; Dong Meiting; Li Ziqing; Zheng Xuwei; Yang Yujie; Su Zuqing; Li Shaoping; Lu Chuanjian (Carbohydrate Polymers, 2025)

Design, synthesis, and molecular docking study of isopimaroyl 1,2,4-triazole-thioether derivatives as anti-tumor agents - Juanjuan Liu; Ya Gao; Hu Chen; Guoyong Luo; Shaoping Yang (Natural Product Research, 2025)

Research Progress on bioactive peptides from animal sources: A comprehensive review - Jiteng Sun; Yanli Chen; Yue Yang; Haixia Chen; Jiayu Zhang; Shaoping Wang; Daoming Bai; Zhiqiang Sun; Jing Song; Long Dai (Food Chemistry, 2025)

TRIM22 in Litopenaeus vannamei activates Dorsal by accelerating Cactus's degradation to mediate antiviral immunity - Xuanzheng Di; Hao Yang; Airong Lv; Xiaodi Wang; Ruiying Li; Ranran Wang; Bin Yin; Sheng Wang; Shaoping Weng; Chaozheng Li; Jianguo He; Haoyang Li (Fish & Shellfish Immunology, 2025)

A Low-FODMAP diet enhances IBS symptom relief and gut microbiota homeostasis: A meta-analysis - Wanyu Yang; Huizi Tan; Shaoping Nie (Food Bioscience, 2025)

Regulatory Mechanism of CRTC1 on Autophagy and GluA2 Expression in Epilepsy - Xueying Wang; Liqian Zhou; Lin Yang; Shaoping Huang; Yuying Wang; Dan Li (Molecular Neurobiology, 2025)

Precise A·T-to-G·C Base Editing in Banana - Shaoping Wu; Chunhua Hu; Haocheng Zhu; Jinxing Liu; Tongxin Dou; Fei Qin; Binhui Yin; Fangcheng Bi; Qiaosong Yang; Ganjun Yi (Journal of Plant Growth Regulation, 2025)

A cytokine receptor domeless restrains mud crab reovirus infection via JAK-STAT signaling pathway in mud crab (Scylla paramamosain) - Hengwei Deng; Yetong Ke; Shaoping Weng; Lei Hu; Wenfeng Zhang; Yujia Sun; Linwei Yang; Xuewen Wang; Mingyang Feng; Weiliang Guo; Zhihong Zhong; Dongdong Zhang; et al. (Fish & Shellfish Immunology, 2025)

Constructing single-atom Rh sites for selective hydroformylation of 1,3-butadiene to adipic aldehyde - Zhaozhan Wang; Zihao Yang; Yifan Liu; Shingo Hasegawa; Ken Motokura; Shaoping Kuang; Yong Yang (Chemical Engineering Journal, 2025)

Establishment and characterization of a novel cell line derived from spotted sea bass Lateolabrax maculatus and its susceptibilities to iridoviruses - Zhipeng Zhan; Xueqian Cao; Jie Su; Yangchi Cui; Yang Zheng; Pengli Xiao; Zhoutao Lu; Shaoping Weng; Changjun Guo; Jianguo He (Aquaculture, 2025)

Multi-targeted pharmacological properties of cinnamyl piperazine derivatives: a comprehensive review - Yongqi Wang; Mengchen Lei; Zefeng Zhao; Shaoping Wu; Xiaohui Zheng; Haifa Qiao; Xiaohang Yang (Medicinal Chemistry Research, 2025)

A novel perlucin with immune regulatory functions protects Litopenaeus vannamei against Vibrio parahaemolyticus infection - Zi-ang Wang; Linwei Yang; Zexu Zhao; Shaoping Weng; Jianguo He; Xiaopeng Xu (Fish & Shellfish Immunology, 2024)

Multigenerational effects of disperse blue 79 at environmentally relevant concentrations on zebrafish (Danio rerio) fecundity: An integrated approach - Chao Wang; Wen Gu; Shaoping Zhang; Li Li; Jian Kong; Hong Zhi; Juan Liu; Mengmeng Wang; Ke Miao; Qi Li; Jie Yu; Runming Wang; et al. (Journal of Hazardous Materials, 2024)

Evaluation of the anti-atherosclerotic effect for Allium macrostemon Bge. Polysaccharides and structural characterization of its a newly active fructan - Pei Lin; Qiqi Wang; Qi Wang; Jiayun Chen; Liangliang He; Zifei Qin; Shaoping Li; Jingyan Han; Xinsheng Yao; Yang Yu; Zhihong Yao (Carbohydrate Polymers, 2024)

BnaPLDα1-BnaMPK6 Involved in NaCl-Mediated Overcoming of Self-Incompatibility in Brassica napus L. - Yuanyuan Li; WenXuan Zhang; Yong Yang; Xiaomei Liang; Shaoping Lu; Chaozhi Ma; Cheng Dai (Plant Science, 2024)

Integrated metabolomics and transcriptomics to study mechanisms of Paecilomyces cicadae-fermented Radix astragali in the treatment of hyperuricemia - Hong Wang; Yufan Tao; Yifang Cui; Xianming Lan; Shuyi Song; Zhonglei Zhang; Shaoping Wang; Ailin Yang; Jiayu Zhang (Food Bioscience, 2024)

Multi-omics insights into biogeochemical responses to organic matter addition in an acidic pit lake: Implications for bioremediation - Zhixiang She; Jin Wang; Xin Pan; Ding Ma; Yijun Gao; Shaoping Wang; Xin Chuai; Yang Mu; Zhengbo Yue (Water Research, 2024)

Orange-spotted grouper IFNh response to NNV or MSRV and its potential antiviral activities - Siyou Huang; Rui Zheng; Yiling Kang; Linwei Yang; Jie Gao; Qingqing Liu; Shaoping Weng; Jianguo He; Junfeng Xie (Fish & Shellfish Immunology, 2024)

Preliminary Results of the Seismicity Monitoring Experiment around the 2019 Mw5.4 Earthquake Epicenter in the Central South China Sea Basin - Wenfei Gong; Aiguo Ruan; Xiongwei Niu; Zhenjie Wang; Pingchuan Tan; Xiaodong Wei; Wei Wang; Zhengyi Tong; Liqun Cheng; Fansheng Kong; Shaoping Lu; Jianke Fan; et al. (Journal of Earth Science, 2024)

The structure of anthocyanins and the copigmentation by common micromolecular copigments: A review - Jiadong Wang; Yanqiao Zhao; Bing Sun; Yutong Yang; Shaoping Wang; Zirui Feng; Jianying Li (Food Research International, 2024)

The mediating role of exhaled breath condensate metabolites in the effect of particulate matter on pulmonary function in schoolchildren: A crossover intervention study - Xiaoyan Yang; Dongqun Xu; Bo Wen; Jian Ji; Zeyu Zhang; Li Li; Shaoping Zhang; Hong Zhi; Jian Kong; Chong Wang; Jun Wang; Hongjie Ruan; et al. (Science of The Total Environment, 2023)

Basigin binds bacteria and activates Dorsal signaling to promote antibacterial defense in Penaeus vannamei - Linwei Yang; Zi-ang Wang; Yushi Gan; Hongliang Zuo; Hengwei Deng; Shaoping Weng; Jianguo He; Xiaopeng Xu (Fish & Shellfish Immunology, 2023)

Polysaccharides from small black soybean alleviating type 2 diabetes via modulation of gut microbiota and serum metabolism - Zhouya Bai; Xiaojun Huang; Guangjie Wu; Yanli Zhang; Hedi Xu; Yang Chen; Huayu Yang; Shaoping Nie (Food Hydrocolloids, 2023)

The Hippo-Yki pathway downstream transcription factor Scalloped negatively regulates immune defense against Vibrio parahaemolyticus infection in shrimp - Linwei Yang; Deyu Han; Zi-ang Wang; Nuo Chen; Hongliang Zuo; Zhixun Guo; Menghuang Xu; Shaoping Weng; Jianguo He; Xiaopeng Xu (Fish & Shellfish Immunology, 2023)

Analysis of the dynamic mechanisms of upwelling in deep ocean water caused by typhoons - Famei Lei; Hao Dai; Shaoping Shang; Zhigang He; Shuai Yang (Ocean Dynamics, 2023)

A novel Toll receptor from Pacific white shrimp Penaeus vannamei is involved in immune defense against Vibrio parahaemolyticus infection - Shengwen Niu; Yuening Zhu; Ran Geng; Nuo Chen; Mengting Luo; Hongliang Zuo; Linwei Yang; Shaoping Weng; Jianguo He; Xiaopeng Xu (Aquaculture, 2023)

Hepatic metabolism-related effects of polysaccharides from red kidney bean and small black soybean on type 2 diabetes - Zhouya Bai; Xiaojun Huang; Guangjie Wu; Yujia Zhou; Xingchao Deng; Jingrui Yang; Junyi Yin; Shaoping Nie (Food Chemistry, 2023)

GoogLeNet based on residual network and attention mechanism identification of rice leaf diseases - Le Yang; Xiaoyun Yu; Shaoping Zhang; Huibin Long; Huanhuan Zhang; Shuang Xu; Yuanjun Liao (Computers and Electronics in Agriculture, 2023)

A novel chitinase Chi6 with immunosuppressive activity promotes white spot syndrome virus (WSSV) infection in Penaeus vannamei - Shengwen Niu; Yuening Zhu; Ran Geng; Mengting Luo; Hongliang Zuo; Linwei Yang; Shaoping Weng; Jianguo He; Xiaopeng Xu (Fish & Shellfish Immunology, 2023)

Alpha-aminoisobutyric acid incorporated peptides for the construction of electrochemical biosensors with high stability and low fouling in serum - Xiqin Yang; Min Chen; Zhanhua Zhang; Yang Li; Peipei Wang; Xiliang Luo; Shaoping Lv (Analytica Chimica Acta, 2023)

Association between short- and long-term exposures to air pollutants and internalizing/externalizing behavior in children aged 4 to 7 years - Haiqin Qi; Anna Peng; Hong Mei; Yuanyuan Zhang; Ya Zhang; Paiziyeti Tuerxun; Wenli Dong; Chunan Li; Ke Xu; Ruixia Chang; Shaoping Yang; Jianduan Zhang (Environmental Science and Pollution Research, 2022)

Impact of waste of COVID-19 protective equipment on the environment, animals and human health: a review - Sheng Yang; Yanping Cheng; Tong Liu; Shaoping Huang; Lihong Yin; Yuepu Pu; Geyu Liang (Environmental Chemistry Letters, 2022)

Verification of Vibration Isolation Effectiveness of the Underwater Vehicle Power Plant - Yang Yang; Guang Pan; Shaoping Yin; Ying Yuan; Qiaogao Huang (Journal of Marine Science and Engineering, 2021)
In order to enhance the vibration isolation effectiveness of an underwater vehicle power plant, and alleviate the mechanical vibration of the outer housing, initially discrete vibration isolators were improved, and three new types of ring vibration isolators designed, i.e., ring metal rubber isolators, magnesium alloy isolators and modified ultra-high polyethylene isolators (MUHP). A vibrator excitation test was carried out, and the isolation effectiveness of the three types of vibration isolators was evaluated, adopting insertion loss and vibration energy level drop. The results showed that compared with the initial isolators and the other two new types of isolators, MUHP showed the most significant vibration isolation effectiveness. Furthermore, its effectiveness was verified by a power vibration test of the power plant. To improve the vibration isolation effectiveness, in addition to vibration isolators, it is essential to carry out investigations on high-impedance housings.

Risks of maternal prepregnancy overweight/obesity, excessive gestational weight gain, and bottle-feeding in infancy rapid weight gain: evidence from a cohort study in China - Shaoping Yang; Hong Mei; Hui Mei; Yan Yang; Na Li; Yafei Tan; Yiming Zhang; Dan Zhang; Yan Zhang; An’na Peng; Bin Zhang (Science China Life Sciences, 2019)

The Sesuvium portulacastrum Plasma Membrane Na+/H+ Antiporter SpSOS1 Complemented the Salt Sensitivity of Transgenic Arabidopsis sos1 Mutant Plants - Yang Zhou; Xiaochang Yin; Shumin Wan; Yanping Hu; Qing Xie; Ruimei Li; Baibi Zhu; Shaoping Fu; Jianchun Guo; Xingyu Jiang (Plant Molecular Biology Reporter, 2018)

The novel Na+/H+ antiporter gene SpNHX1 from Sesuvium portulacastrum confers enhanced salt tolerance to transgenic yeast - Yang Zhou; Chenglong Yang; Yanping Hu; Xiaochang Yin; Ruimei Li; Shaoping Fu; Baibi Zhu; Jianchun Guo; Xingyu Jiang (Acta Physiologiae Plantarum, 2018)

Isolation and characterization of a C-repeat binding factor (CBF)-like gene in cassava (Manihot esculenta Crantz) - Ruimei Li; Yimeng Ji; Jie Fan; Chenglong Yang; Yuan Yao; Yang Zhou; Ruijun Duan; Jiao Liu; Shaoping Fu; Xinwen Hu; Jianchun Guo (Acta Physiologiae Plantarum, 2014)

ORF005L from infectious spleen and kidney necrosis virus is located in the inner mitochondrial membrane and induces apoptosis - Rui Wang; Yang Yi; Lihong Liu; Yanghong Lu; Shaoping Weng; Jianguo He; Xiaopeng Xu (Virus Genes, 2014)

Polymer-Mediated Anti-solvent Crystallization of Nitrendipine: Monodispersed Spherical Crystals and Growth Mechanism - Dengning Xia; Mei Ouyang; Jian X. Wu; Yanbo Jiang; Hongyu Piao; Shaoping Sun; Li Zheng; Jukka Rantanen; Fude Cui; Mingshi Yang (Pharmaceutical Research, 2012)

Identification of Juxtanodin promoter and its transcriptional regulation during the ATRA-induced differentiation of C6 cells - Tao Wang; Lintao Jia; Guodong Yang; Shaoping Ji; Libo Yao; Bin Zhang (Molecular and Cellular Biochemistry, 2011)

Transformation of Lead Solid Fraction in the Rhizosphere of Elsholtzia splendens: The Importance of Organic Matter - Jianjun Yang; Shaoping Hu; Xincai Chen; Mingge Yu; Jin Liu; Hang Li; Chaofeng Shen; Jiyan Shi; Yingxu Chen (Water, Air, & Soil Pollution, 2010)

Genetic and physical localization of an anthracnose resistance gene in Medicago truncatula - Shengming Yang; Muqiang Gao; Shweta Deshpande; Shaoping Lin; Bruce A. Roe; Hongyan Zhu (Theoretical and Applied Genetics, 2007)

A disjoint algorithm for seismic reliability analysis of lifeline networks - Yang Han; Shaoping Sun (Earthquake Engineering and Engineering Vibration, 2002)